2021
DOI: 10.3390/foods10081766
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Validation of the Food Neophobia Scale: The Case of Hungary

Abstract: Food neophobia is the fear or loathing of novel food, which may result in the rejection of the unfamiliar food item. The most frequently used and most reliable tool to measure adult food neophobia is the Food Neophobia Scale (FNS), which has been translated into several languages, making it possible to compare food neophobia levels around the world. The main objective of this research has been the adaptation and validation of the FNS in Hungary. In order to achieve the research objectives, a questionnaire surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 47 publications
(227 reference statements)
1
8
1
Order By: Relevance
“…The high internal consistency also indicated that the total score of the Malay-translated version of the FNS was able to represent the extent of food neophobia and that the scale was reliable. Our findings align with other adaptation and validation studies of the FNS, which have consistently exhibited good internal consistency, with Cronbach's alphas more than .8 (Szakály et al, 2021;de Andrade Previato & Behrens, 2015;Elmas & Kabaran, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The high internal consistency also indicated that the total score of the Malay-translated version of the FNS was able to represent the extent of food neophobia and that the scale was reliable. Our findings align with other adaptation and validation studies of the FNS, which have consistently exhibited good internal consistency, with Cronbach's alphas more than .8 (Szakály et al, 2021;de Andrade Previato & Behrens, 2015;Elmas & Kabaran, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This skewed gender distribution and sociodemographic background may limit the generalizability of the study’s results to more diverse populations, but our robust sample size supports our construct validity and reliability findings, as we maintained a 1:10 ratio of questions to respondents. Additionally, the EFA is a subjective and inductive process where, for example, factor labelling depends on the researchers’ definition based on previous literature (Choe & Cho, 2011; Szakály et al, 2021). Therefore, future studies may consider a confirmatory factor analysis with larger samples from different age groups of Malaysian adults to test how well the data fit with the proposed model or theory and to further confirm the EFA result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tourists as neophiliacs are more likely to experience positive emotions through unfamiliar foods and flavors that they recognize as typical of the destination [39]. Food neophiliacs view the experience of seeking out new flavors and ingredient combinations as a positive adventure, and as a natural part of the trip [40] and will try any kind of food since their choices are mainly generated by curiosity [41]. Hence, experiencing local cuisine novelty ends up making a decisive contribution to the positive experience at the destination [5].…”
Section: Food Neophilia and Tourismmentioning
confidence: 99%
“…The 5-point Likert scale (1 = Totally disagree; 2 = Disagree; 3 = Neither agree nor disagree; 4 = Agree; 5 = Totally agree) was used to indicate their agreement with each item. Based on FNS total scores, consumers were classified in the neophile group (if the consumer FNS value was lower than the FNS total score minus standard deviation), neutral group (consumer FNS value higher than FNS total score minus standard deviation but lower than FNS total score plus standard deviation), and neophobic group (consumer FNS value higher than FNS total score plus standard deviation), as described by Szakály et al (2021).…”
Section: Sensory Evaluationmentioning
confidence: 99%